A unique case of ectopic pancreas presenting as jejunal malignance. Issue 7 (11th July 2019) - Zhang, Peng; Wang, Mojin; Bai, Lifen; Zhuang, Wen
Abstract: Ectopic pancreas is defined as pancreatic tissues having no anatomic or vascular connections with the orthotopic pancreas. It is difficult for clinicians to diagnose this disease without performing a histopathological examination because it lacks specific clinical manifestations. This case report is of a 46-year-old woman who presented with epigastric pain. She had elevated serum levels of carcinoembryonic antigen (CEA) and carbohydrate antigen 72-4 (CA72-4). Abdominal contrast-enhanced computed tomography (CT) revealed a persistently enhanced mass in the proximal jejunum, which was confirmed as ectopic pancreas via histopathological examination. Her serum CEA and CA72-4 levels were restored to normal ranges after resecting the jejunal ectopic pancreas. This is the first reported case of ectopic pancreas causing an elevation in serum CEA and CA-724 levels; this report supports the metaplasia theory and suggests that jejunal masses should be cautiously diagnosed for avoiding unnecessary concerns among patients and their families.